Faktor – Faktor yang Berhubungan dengan Kecelakaan Lalu Lintas pada Karyawan Pengendara Sepeda Motor di Koperasi Simpan Pinjam (KSP) Sumber Rejeki Blora - Devi Eka Meirinda; Suroto Suroto; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Traffic accident is world problem. Almost year to year occur increase until 5%. Traffic accident at highway is dangerous to all employees who have high mobility, such as Koperasi Simpan Pinjam’s employee must work past the road with long distance every day. The purpose of this research is knowing factors associated with traffic accident on employees who use motorcyle at Koperasi Simpan Pinjam (KSP) Sumber Rejeki Blora. This research use analytical descriptive methode with cross sectional approach. Number of respondents who entered the survey is 40 respondents. All of them are Koperasi Simpan Pinjam (KSP) Sumber Rejeki Blora’s employees who ride motorcycle during working. This research use instruments, that are questionnare and data analysis with Chi-Square test. The result of this research are present two significant relationship that assosiate with traffic accident. That are drive speed (p=0.031) and exhaustion (p=0.044). The others factors such as age (p=0.707), working time (p=0.928), factor of vehicles (p=0.695), and factor of environment (p=0,533) have not significant relationship with traffic accident on Koperasi Simpan Pinjam (KSP) Sumber Rejeki Blora’s employees. Conclusion can be obtained from this research is factors associated with traffic accident on employees who use motorcyle at Koperasi Simpan Pinjam (KSP) Sumber Rejeki Blora are drive speed and exhaustion.